Implementation strategies for web-based applications for screening: a scoping review - Chor, Yau Ooi; Chirk, Jenn Ng; Sales, Anne E.; Lim, H.M. (2019)
1. Chor Yau Ooi, Chirk Jenn Ng, Anne E. Sales, & Lim, H. M.